Analisis Perilaku Belajar Siswa Hiperaktif dalam Pembelajaran Matematika - Asdar; Nasrullah; Alya Dian Sari (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2021)
This study aims to determine the characteristics of hyperactive student learning behavior in mathematics. This is a descriptive qualitative research. The data collection methods werethe observation, interview, and documentation. The research instrument was the observation sheet, interview guidelines, and the researcher himself. The data analysis techniques are data reduction, data presentation, and drawing conclusions. The results of the study showed that 1) the cognitive learning behavior of hyperactive students, especially in the topic about exponent. There are several behaviors that are indicated, namely: a. given a quiz, students are able to use their reasoning and to develop their own knowledge about the answers to the problems given, even though the results of students' answers are wrong, b. students cannot solve mathematical problems that are the calculation of rank multiplication, division of rank, and the nature of the other ranks, c. students are slow in accepting learning material, d. students cannot concentrate on the process of learning mathematics, he tends to draw pictures or doodle on his book. 2) the affective learning behavior of hyperactive students shown, namely: a. when the learning process students often leave their seats and often hit their friends suddenly, and speak without control, b. students cannot be held responsible when leading a group discussion, c. students often violate school rules.